1990
DOI: 10.1111/j.1540-5915.1990.tb00326.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Two Screen/Report Design Variables in an Information Recall Context*

Abstract: This paper considers the question of how much time and effort should be spent in preparing a bid for a single item of known value sold at a first-price sealed-bid auction. A decision-theoretic approach to this bid decision summarizes the decision maker's knowledge of the competitive environment through his or her subjective probability distribution of the highest competing bid. Research activities such as collecting and analyzing bid histories are efforts to obtain additional information that reduces the uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Similarly, studies have found that presentation format affects recall (Metcalfe et al, 1981;Umanath et al, 1990;Clements and Wolfe, 1998;Umanath et al, 1998;Hodge et al, 2004;Nouri and Douglas Clinton, 2006). The results of such studies are consistent.…”
Section: Satisfaction Persuasion and Recallsupporting
confidence: 52%
“…Similarly, studies have found that presentation format affects recall (Metcalfe et al, 1981;Umanath et al, 1990;Clements and Wolfe, 1998;Umanath et al, 1998;Hodge et al, 2004;Nouri and Douglas Clinton, 2006). The results of such studies are consistent.…”
Section: Satisfaction Persuasion and Recallsupporting
confidence: 52%
“…Just as information presentation formats can be defined as spatial or symbolic, the most prominent categorization of task type within information presentation research also involves the distinction between symbolic and spatial task processing (Umanath et al, 1990;Vessey, 1991). Symbolic tasks require the recall or identification of precise data values (e.g., what were 2Q 2005 net sales for Amazon?)…”
Section: Cognitive Fit Theorymentioning
confidence: 99%
“…Symbolic tasks require the recall or identification of precise data values (e.g., what were 2Q 2005 net sales for Amazon?) (Umanath et al, 1990). Alternatively, spatial tasks assess the problem area more holistically and often involve trend analysis or other types of information associations (e.g., Are Amazon's s net sales improving, stable, or decreasing over the last four quarters?)…”
Section: Cognitive Fit Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The dual coding theory has been applied successfully to understand the effectiveness of verbal versus imagery presentation modes in a wide range of contexts, including computer assisted learning (Lalley, 1998), printed advertisements (Unnava and Burnkrant, 1991), individual creativity support systems (Malaga, 2000), and decision support systems (Umanath et al, 1990). …”
Section: The Dct and Presentation Modementioning
confidence: 99%